The secret, book & scone society - Adams, Ellery (Adams, Ellery. Secret, Book, and Scone Society novel, 2017)
Strangers flock to Miracle Springs hoping the natural hot springs, five-star cuisine, and renowned spa can cure their ills. If none of that works, they often find their way to Miracle Books, where, over a fresh-baked “comfort” scone, they exchange their stories with owner Nora Pennington in return for a carefully chosen book. That<U+2019>s Nora<U+2019>s special talent<U+2014>prescribing the perfect novel to ease a person<U+2019>s deepest pain. So when a visiting businessman reaches out for guidance, Nora knows exactly how to help. But before he can keep their appointment, he<U+2019>s found dead on the train tracks. Stunned, Nora forms the Secret, Book, and Scone Society, a group of damaged souls yearning to earn redemption by helping others. To join, members must divulge their darkest secret<U+2014>the terrible truth that brought each of them to Miracle Springs in the first place. Now, determined to uncover the truth behind the businessman<U+2019>s demise, the women meet in Nora<U+2019>s cozy bookstore. And as they untangle a web of corruption, they also discover their own courage, purpose, and a sisterhood that will carry them through every challenge<U+2014>proving it<U+2019>s never too late to turn the page and start over<U+2026>